2008
DOI: 10.1007/s00126-008-0181-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluid and source magma evolution of the Questa porphyry Mo deposit, New Mexico, USA

Abstract: Combined fluid inclusion microthermometry and microanalysis by laser ablation inductively coupled plasma mass spectrometry (LA-ICPMS) are used to constrain the hydrothermal processes forming a typical Climax-type porphyry Mo deposit. Molybdenum mineralisation at Questa occurred in two superimposed hydrothermal stages, a magmatic-hydrothermal breccia and later stockwork veining. In both stages, texturally earliest fluids were single-phase, of low salinity (~7 wt.% NaCl equiv. ) and intermediate-density. Upon de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(127 citation statements)
references
References 35 publications
8
106
2
Order By: Relevance
“…As for fluid boiling, however, it has been recently suggested that it is not a major cause for Mo precipitation in many porphyry Mo deposits [13]. This is because the initial supercritical (single-phase) fluid has a relatively low salinity (e.g., ∼7 wt% NaCl equiv [2,56,59]), and the two-phase field is intersected on the vapor limb once boiling occurs; that is, brine will condense out of a vapor-like bulk fluid, rather than the other way around. In this case the condensation of small amounts of brine out of a vapor-like bulk fluid should not significantly influence the properties of the bulk system, and therefore fluid boiling in the porphyry Mo system is unlikely associated with metal precipitation [13].…”
Section: Hydrothermal Evolution and Metal Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for fluid boiling, however, it has been recently suggested that it is not a major cause for Mo precipitation in many porphyry Mo deposits [13]. This is because the initial supercritical (single-phase) fluid has a relatively low salinity (e.g., ∼7 wt% NaCl equiv [2,56,59]), and the two-phase field is intersected on the vapor limb once boiling occurs; that is, brine will condense out of a vapor-like bulk fluid, rather than the other way around. In this case the condensation of small amounts of brine out of a vapor-like bulk fluid should not significantly influence the properties of the bulk system, and therefore fluid boiling in the porphyry Mo system is unlikely associated with metal precipitation [13].…”
Section: Hydrothermal Evolution and Metal Depositionmentioning
confidence: 99%
“…In some of these deposits Mo is recovered as byproduct (i.e., porphyry Cu-Mo (±Au) deposits), whereas, in others, the deposits are characterized by high abundances of Mo but virtually no Cu or Au (i.e., purely porphyry Mo deposits) such as the Climax-type deposits along the North American Cordillera [1][2][3]. China has more than half of the world's molybdenum metal [4], and many of the Mo deposits are similar to the Climax-type Mo deposits where molybdenite is almost the only sulfide [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Climax-type deposits, the earliest fluids were singlephase, CO 2 -bearing aqueous fluids, were of low salinity and intermediate density, and were released from the evolving magma from mid-crustal to lower crustal level; by decompression from near-lithostatic to near-hydrostatic conditions, they boiled off a vapor phase, leaving behind a residual brine that ponded in the roof region of the granite porphyry; Mo precipitated from a dense, residual and probably sulfide-depleted brine, in response to cooling of the saline liquid from 420 °C to 350 °C (Klemm et al 2008). By contrast, the Yaochong porphyry Mo system was formed with a large number of PC-and C-type inclusions in the minerals in earlier stages (Table 4).…”
Section: Comparison With Climax-type Mo Depositsmentioning
confidence: 99%
“…This alteration feature is shared by all the Mesozoic porphyry Mo systems in the East Qinling and Dabie Shan, such as the deposits at Yuchiling (li et al 2012c), Jinduicheng (Yang et al 2009), nannihu , Tangjiaping (Chen and Wang 2011), and Qian'echong . ); Jingduicheng (Yang et al 2009) Climax (Hall et al 1974) Henderson (Seedorff and Einaudi 2004a, b;Wallace et al 1978) Urad (Wallace et al 1978) Questa (Cline and Bodnar 1994;Klemm et al 2008) 1 3…”
Section: Comparison With Climax-type Mo Depositsmentioning
confidence: 99%